“Legislative cyber-forgetfulness” in Peru: problematic impacts of recent amendments to the Organized Crime Act on cybercrime in light of the Palermo Convention - Velásquez Pasapera, Mirella Estilita (2025)
The main objective of this research is to highlight the legal setback that, due to its discrepancies with the Palermo Convention, the latest amendments to the Organized Crime Act have brought with them, in relation to two of the most common crimes in the Peruvian cybercrime context: computer fraud and identity theft. The relevance of this issue is not only evident in the current relevance of the problem, but also because it invites us to reflect on the degree of binding force of the provisions contained in instruments such as the Palermo Convention. The main result of this study is the clear contrast between some of the amendments introduced in the Organized Crime Act and elements of the Palermo Convention, particularly when the Peruvian Act requires the subject's continued presence and integration in the organized criminal group and establishes a higher threshold for seriousness than that provided for in the Convention. These legislative reforms not only call into question the binding nature of the treaty provisions for the States Parties, but also, under Peruvian domestic law, impede the investigation of criminal organizations engaged in identity theft and/or computer fraud.